2020
DOI: 10.17305/bjbms.2020.4538
|View full text |Cite
|
Sign up to set email alerts
|

Association of miRNA-145 with the occurrence and prognosis of hydrosalpinx-induced defective endometrial receptivity

Abstract: MiR-145 is reported to facilitate inflammation and is also associated with unsuccessful embryonic implantation. Whether miR-145 mediates inflammatory response underlying hydrosalpinx-induced defective endometrial receptivity (ER) remains unclear, and this study attempted to clarify this point. Endometrium samples were collected from hydrosalpinx patients (case, n = 243) and patients with tubal patency/obstruction (control, n = 187). The peripheral blood samples of cases and controls were collected to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In another study, of 667 miRNAs that were studied in women with endometriosis, two miRNAs including miR-483-5p and miR-629 were highly downregulated in patients compared with controls and the authors of this study considered these miRNAs to have an important role in an early defect in the physiological activity of the proliferative endometrium, which eventually would lead to endometriosis ( 22 ). The importance of miRNAs including miR-145 ( 23 , 24 ), miR-200b-3p ( 25 ), miR-92a ( 26 ), mir-185-5p ( 27 ), microRNA-520 ( 28 ), and miRNA-125b ( 29 ) has been indicated in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, of 667 miRNAs that were studied in women with endometriosis, two miRNAs including miR-483-5p and miR-629 were highly downregulated in patients compared with controls and the authors of this study considered these miRNAs to have an important role in an early defect in the physiological activity of the proliferative endometrium, which eventually would lead to endometriosis ( 22 ). The importance of miRNAs including miR-145 ( 23 , 24 ), miR-200b-3p ( 25 ), miR-92a ( 26 ), mir-185-5p ( 27 ), microRNA-520 ( 28 ), and miRNA-125b ( 29 ) has been indicated in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from both experimental and clinical studies suggest that miRNA-145 differentiated levels in patients' serum could serve as an essential biomarker for AAA detection and progression (23). Single nucleotide polymorphisms (SNPs) in miRNA genes (miR-SNPs) could affect miRNA function via either altering transcription of the primary miRNA transcript, or processing of the pri-miRNA and pre-miRNA or by influencing miRNA-mRNA interactions (24)(25)(26)(27); thus, miR-SNPs are implicated in the development of various diseases (28,29). Although a possible link between miRNA-145 and AAA has been indicated, there is no published data regarding the association of miRNA-145 genetic polymorphisms with AAA susceptibility.…”
Section: Association Of Mirna-145 Single Nucleotide Polymorphisms In ...mentioning
confidence: 99%
“…Studies have shown that hydrosalpinx may interfere with embryo implantation by affecting endometrial receptivity [5][6][7]. The possible mechanisms include mechanical scour caused by uid re ux [8], toxic effects of hydrops on embryos [5,7,9], and effects of hydrops on endometrial receptivity [10][11][12]. In addition, enlarged uid can also affect ovarian function.…”
Section: Introductionmentioning
confidence: 99%